The indicators of the bone tissue mineralization abnormalities in women with coronary artery disease in the post-menopausal period - Mykhailovska, N. S.; Stetsiuk, І. О.; Михайловська, Наталія Сергіївна; Стецюк, Ірина Олегівна; Михайловская, Н. С.; Стецюк, И. О. (Запорізький державний медичний університет, 2018)
Objective. To determine the indicators of the bone mineral density (BMD) abnormalities in women with coronary artery disease (СAD) in the post-menopausal period. Methods. An open cross-sectional study in parallel groups involved 80 women with coronary artery disease (CAD): stable exertional angina of II–III functional class (mean age 64.59 ± 1.02 years). Depending on the degree of BMD they were divided into 3 groups: group 1 – 19 CAD women with normal BMD; group 2 – 27 CAD women with osteopenia; group 3 – 34 CAD women with osteoporosis. The control selected group consisted of 11 healthy women of the corresponding age. With the help of ultrasound densitometry, FRAX algorithm and bone biomarkers levels assessment we investigated structural and functional state of the bone tissue. Results. It was acknowledged that in women with CAD in the postmenopausal period, depending on the severity of BMD loss, there is a significant decrease in the T- and Z-criteria and an increase in the 10-year risk of developing osteoporosis fractures. The development of postmenopausal osteoporosis (PMOS) combined with CAD was accompanied with an increase in the level of inflammation, neoangiogenesis and bone remodeling biomarkers (osteoprotegerin, ostecalcin, VEGF-A), which also have multi-directional correlative interrelationships with the structural and functional indicators of the BMD state (T, Z-criterion, 10-year risk of osteoporosis fractures). ROC-analysis results show the cut-off values at the osteopenia and osteoporosis stage for osteoprotegerin level equal to 223.76 pg/ml and 224.44 pg/ml; for osteocalcin level – 15.89 ng/ml and 16.71 ng/ml, for VEGF-A level – 112.52 pg/ml and 123.31 pg/ml correspondingly. Conclusions. The levels of osteoprotegerin and/or ostecalcine and/or VEGF-A can be used as a screening method for early diagnosis of BMD loss and stratification of patients in the category of increased risk of osteopenia and osteoporosis. Мета роботи – визначити індикатори порушення мінеральної щільності кісткової тканини (МЩКТ) у жінок у постмено-паузальному періоді, які хворі на ішемічну хворобу серця (ІХС). Матеріали та методи. У відкрите поперечне дослідження в паралельних групах залучили 80 жінок із діагнозом ІХС: стенокардія напруги ІІ–ІІІ ФК (середній вік – 64,59 ± 1,02 року). Залежно від стану МЩКТ хворих поділили на 3 групи: 1 – 19 жінок із нормальними показниками МЩКТ; 2 – 27 жінок з остеопенією; 3 – 34 жінки з остеопорозом. Контрольна група – 11 здорових жінок відповідного віку. За допомогою ультразвукової остеоденситометрії, алгоритму FRAX та оцінювання рівня кісткових біомаркерів вивчили структурно-функціональний стан кісткової тканини. Результати. У жінок, хворих на ІХС, у постменопаузальному періоді залежно від ступеня вираженості порушень МЩКТ спостерігали вірогідне зниження Т- та Z-критеріїв і збільшення 10-річного ризику розвитку остеопорозних переломів. Розвиток постменопаузального остеопорозу (ПМОП) на тлі ІХС супроводжувався підвищенням рівня біомаркерів запалення, неоангіогенезу та кісткового ремоделювання (остеопротегерину, остекальцину, ВЕФР-А), участь яких у процесах кісткового ремоделювання підтверджувалась наявністю кореляційних взаємозв’язків із показниками, що відбивають структурно-функціональний стан кісток (Т-, Z-критерії, 10-річний ризик розвитку остеопорозних переломів). За допомогою ROC-аналізу визначено критичні точки рівня біомаркерів кісткового ремоделювання щодо розвитку остеопенії та остеопорозу, які для рівня остеопротегерину становили 223,76 пг/мл та 224,44 пг/мл, для рівня остеокальцину – 15,89 нг/мл та 16,71 нг/мл, для рівня ВЕФР-А – 112,52 пг/мл та 123,31 пг/мл відповідно. Висновки. Визначені за допомогою ROC-аналізу рівні остеопротегерину та/або остекальцину та/або ВЕФР-А можуть бути використані для ранньої діагностики порушень структури кісткової тканини та стратифікації хворих у категорію підвищеного ризику розвитку остеопенії та остеопорозу. Цель работы – определить индикаторы нарушения минеральной плотности костной ткани (МПКТ) у женщин в постменопаузальном периоде, страдающих ишемической болезнью сердца Материалы и методы. В открытое поперечное исследование в параллельных группах включили 80 женщин с диагнозом ИБС: стенокардия напряжения ІІ–ІІІ ФК (средний возраст – 64,59 ± 1,02 года). В зависимости от состояния минеральной плотности костной ткани (МПКТ) все больные разделены на 3 группы: 1 – 19 женщин нормальными показателями МПКТ; 2 – 27 женщин с остеопенией; 3 – 34 женщины с остеопорозом. Контрольную группу составили 11 здоровых женщин соответствующего возраста. С помощью метода ультразвуковой остеоденситометрии, алгоритма FRAX и оценки уровня костных биомаркеров исследовано структурно-функциональное состояние костной ткани. Результаты. У женщин, страдающих ИБС, в постменопаузальном периоде в зависимости от степени выраженно¬сти нарушений МПКТ отмечено достоверное снижение Т- и Z-критериев и увеличение 10-летнего риска развития остеопорозных переломов. Развитие постменопаузального остеопороза (ПМОП) на фоне ИБС сопровождалось повышением уровня биомаркеров воспаления, неоангиогенеза и костного ремоделирования (остеопротегерина, остекальцина, ВЕФР-А), участие которых в процессах костного ремоделирования подтверждается наличием корре¬ляционных взаимосвязей с показателями, отражающими структурно-функциональное состояние костной ткани (Т-, Z-критерии, 10-летний риск развития остеопорозных переломов). При помощи ROC-анализа определены критические точки уровней биомаркеров костного ремоделирования для развития остеопении и остеопороза, которые для уровня остеопротегерина составили 223,76 пг/мл и 224,44 пг/мл, для уровня остеокальцина – 15,89 нг/мл и 16,71 нг/мл, для уровня ВЕФР-А – 112,52 пг/мл и 123,31 пг/мл соответственно. Выводы. Определенные при помощи ROC-анализа уровни остеопротегерина и/или остекальцина и/или ВЕФР-А могут быть использованы в качестве скринингового метода ранней диагностики нарушений структуры костной ткани и стратификации больных в категорию повышенного риска развития остеопении и остеопороза.
Індикатори порушення стану мінералізації кісткової тканини в жінок у постменопаузальному періоді, які хворі на ішемічну хворобу серця
Индикаторы нарушения состояния минерализации костной ткани у женщин в постменопаузальном периоде, страдающих ишемической болезнью сердца
Keywords: coronary artery disease; postmenopausal period; osteoporosis; osteopenia; metabolic diseases; correlation of data; ішемічна хвороба серця; постменопаузальний період; остеопороз; остеопенічний синдром; метаболічні хвороби кісток; взаємозв’язок; ишемическая болезнь сердца; постменопаузальный период; остеопенический синдром; метаболические болезни кости; взаимосвязь